Definição de zonas de manejo utilizando análises multivariadas - Jean Lucas Pereira Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Specific management using a management zone is used on agricultural properties with the aim of maximizing agricultural yield and the application of inputs. However, it is known that to create ZM, soil, climatic and crop variables can be taken into account throughout the development cycle. Therefore, the objective of this project was to delineate management zones using multivariate analysis and the fuzzy c-means algorithm. The experiment was conducted in the Jaboticabal region, São Paulo. To compose the multivariate analyses, chemical and physical parameters of the soil, meteorological variables, vegetation indices and productivity were evaluated. Yield data were obtained from the sampling grid. Meteorological variables were obtained by an automated meteorological station. To obtain vegetation indices, satellite images from the Planet Scope platform were used. After laboratory analysis, the data was subjected to descriptive statistics and correlation analysis was performed to select related attributes to define the management zones. Then, the spatial variability of these attributes was evaluated and spatial distribution maps were created using geostatistical tools. After that, the fuzzy c-means algorithm was performed to delineate ZMs using the MZA software.

O manejo específico utilizando zona de manejo é utilizado em propriedades agrícolas com intuito de maximizar a produtividade agrícola e a aplicação de insumos. Porém, sabe se que para a criação de ZM pode-se levar em consideração diversas variáveis de solo, climáticos e das culturas ao longo do ciclo de desenvolvimento. Dessa forma, objetivou-se com este projeto delinear zonas de manejo utilizando análises multivariadas de e o algoritmo fuzzy c-means. O experimento foi conduzido na região de Jaboticabal, São Paulo. Para compor as análises multivariadas, foram avaliados parâmetros químicos e físicos do solo, variáveis meteorológicas, índices de vegetação e produtividade. Os dados de produtividade foram obtidos no grid de amostragem. As variáveis meteorológicas foram obtidas por estação meteorológica automatizada. Para obtenção dos índices de vegetação, foram utilizadas imagens de satélite da plataforma Planet Scope. Após análises laboratoriais, os dados foram submetidos à estatística descritiva e análise de correlação foi realizada para selecionar os atributos relacionados para definir as zonas de manejo. Em seguida, a variabilidade espacial desses atributos foi avaliada e mapas de distribuição espacial foram elaborados usando ferramentas geoestatísticas. Após isso, o algoritmo de médias c difusas foi executado para delinear ZMs utilizando o software MZA.
Delineation of managetment zones using multivariate analisys
Keywords: Cana-de-açúcar; Agricultura de precisão; Variabilidade espacial; Irrigação